Drake Fontana: capstone - Fontana, Drake, artist (Colorado State University. Libraries, 2013)
The artist's statement: Effective brand communication in today's marketplace is a complex and massive undertaking. With shifting demographics and media platforms the consumer is both more in tune and out of touch with producing brands. The ability to understand this complex cultural landscape of our planet is more important than ever. Through the study of history and design I have attained the skills necessary to effectively comprehend and decipher the complex cultural interactions of our time. This unique mix of visual communication skills and cultural understanding allows me as a designer to make the personal bond between consumer and brand stronger, clearer, more efficient, and longer lasting. A tailored suit always fits better than the mass produced. Design is only as good as the story behind it. I used to think good design was something you learned from a textbook. Do things line up? Is there good use of color and space?; all of the formal artistic requirements. But a brand, a good design, not only captures the attention of an audience, whom doesn't want to listen or be influenced, it lingers in the mind, the subconscious. And for those who care to ask, care to listen, there is a story in the details that embodies the spirit of the entity it represents. The message isn't just simply that 'we are here' and 'this is what we do/offer.' The story is 'this is who we are', 'this is the way we can make your life better.' We want to share ourselves with you, and if you're listening, we hope you like what you hear and come share with us some of you; money, time, or otherwise. It's a true connection between sender and receiver. Something that is personal and genuine. Something that is built on trust, and clarity that generates loyalty. A good story teaches you lessons on life; shows you different perspectives of the world. Whether you agree or disagree is of no confidence, as long as you understand. People don't want to be influenced, but to be influenced is to not have the confidence to say no. A good story doesn't involuntarily impose influence on the audience. In the same way, good design allows for an audience to feel comfortable enough to listen. And once their minds and ears are open hopefully the story is meaningful enough and influential enough to garner a positive reaction of acceptance. Like a good movie or book, good design is a window, an acceptable vehicle to carry a message or lesson to an audience. There are millions of books, movies, designs, and advertisements, but only the good once make an audience want to delve into the details for more. Or come to your destination in the case of advertising.
Colorado State University Art Department capstone project.
Capstone contains the artist's statement and images of works.